Reproduction and fecundity of invader of internal insemination Trachelyopterus galeatus in a Neotropical floodplain (Acta Scientiarum. Biological Sciences, 2021)
After the formation of Itaipu Reservoir, the invader Trachelyopterus galeatus colonized the upper Paraná River. Light microscopy was used to describe gametogenesis and the reproductive phases of females and males. The following data were verified: diameter of the oocytes, spawning type, batch fecundity by ovary weight, standard length, and total weight of the fish, along with the regions where this species reproduced in the upper Paraná River floodplain. A total of 470 specimens were collected quarterly in 2016, 2018 and 2019, and bimonthly in 2017. The gonads were fixed in a Karnovsky solution, dehydrated, infiltrated, and embedded in historesin. The histological slides were stained using PAS + iron hematoxylin + metanil yellow, analyzed and photographed under an image-capturing microscope. As regards diameter of the oocytes and fecundity estimates, ovaries whose oocytes were measured under a stereomicroscope were sampled. In the oogenesis, undifferentiated and differentiated oogonia, early primary growth oocytes, secondary growth oocytes, full-grown oocytes and maturing oocytes were recorded. In the spermatogenesis, primary and secondary spermatogonia, primary and secondary spermatocytes, spermatids and spermatozoa were recorded. The reproductive phases found for females and males were: immature, early development, late development, spawning/sperm-releasing capable, regression, and regeneration. Trachelyopterus galeatus prefers to occupy and reproduce in the Ventura, Patos, Guaraná, Fechada, Garças, and Pau Véio lagoons. The diameter of the oocytes varied from 0.4 to 2.9 mm. Females spawn, on average, 113 oocytes per batch. Batch fecundity variation shows that the larger the ovary, standard length, and total weight, the larger the number of oocytes to be spawned. This invader possesses reproductive success in the upper Paraná River floodplain, especially in lagoons.